Quality of Life and Co-ocurrence of Health Problems in Poor People (2010)
The influence of quality of life in the co-occurrence between health problems and posttraumatic stress disorder (PTSD) was analyzed. The participants were 93 individuals in conditions of forced displacement in Colombia. The measure of the quality of life was composed of the units of consumption and the modified index of relative inequality. Other measures comprised the Davidson Trauma Scale and the General Health Questionnaire. In a structural equation model, it was observed that increasing quality of life reduces co-occurrence, and increasing the scores of PTSD augments co-occurrence, while other health problems have no influence in co-occurrence.